Atypical Lipomatous Tumor/Well-Differentiated Liposarcoma With Features Mimicking Spindle Cell Lipoma. (May 2020) - Jebastin, Judith A. S.; Perry, Kyle D.; Chitale, Dhananjay A.; Mott, Michael P.; Sanchez, Jessica; Fritchie, Karen J.; Palanisamy, Nallasivam; Williamson, Sean R.
Atypical lipomatous tumor/well-differentiated liposarcoma (ALT/WDL) and spindle cell lipoma are lipomatous tumors with distinct clinical, molecular, and prognostic features. Although histological and immunophenotypic features can overlap between ALT/WDL and spindle cell lipoma, the oncogenesis and clinical behavior are markedly different. In borderline cases, molecular analysis for MDM2 or CDK4 amplification can aid in distinguishing ALT/WDL from spindle cell lipoma. Although dedifferentiated liposarcoma has been reported to harbor both MDM2 amplification and loss of the RB1 region, we are not aware of a reported RB1 loss in well-differentiated ALT/WDL. In this article, we present a 69-year-old woman with a lipomatous tumor in the gluteal region that histologically, immunohistochemically, and molecularly mimicked spindle cell lipoma (with positive immunohistochemical staining for CD34 and loss of the RB1 gene region), yet harbored amplification of MDM2 and CDK4 confirmed by fluorescence in situ hybridization, supporting classification as ALT/WDL. This case strengthens the argument that in atypical clinical contexts, molecular studies for MDM2/CDK4 should be considered in tumors resembling spindle cell lipoma.